2022
DOI: 10.1186/s13033-022-00527-w
|View full text |Cite
|
Sign up to set email alerts
|

HIV related stigma associated with social support, alcohol use disorders, depression, anxiety, and suicidal ideation among people living with HIV: a systematic review and meta-analysis

Abstract: Background Stigma is a social phenomenon known to have a negative impact on the lives of people living with HIV (PLWH). However, defining HIV-related stigma (HRS) is difficult because of the intersection it has with structural inequalities, and cultural differences, discrimination by health care providers that measure stigma among PLWH. HIV/AIDS has been characterized as a traumatic experience and PLWH may experience stigma which can cause negative mental health disorders and experiences, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
2
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 102 publications
4
31
2
7
Order By: Relevance
“…Studies showed that stigma is a risk factor for depression in PLHIV, is positively associated with depression [10,11], and is negatively associated with healthy psychological states, such as well-being [12]. A growing body of research shows that social support can reduce HIV-related stigma [13,14]. This suggests that there may be a pathway of social support to reduced depression through reduced stigma [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that stigma is a risk factor for depression in PLHIV, is positively associated with depression [10,11], and is negatively associated with healthy psychological states, such as well-being [12]. A growing body of research shows that social support can reduce HIV-related stigma [13,14]. This suggests that there may be a pathway of social support to reduced depression through reduced stigma [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Studi meta-analysis menunjukkan bahwa adanya hubungan stigma HIV kecemasan (anxiety), depression dan keinginan bunuh diri. Sementara itu, masih dalam studi yang sama, turut menunjukkan bahwa pemberian dukungan sosial akan sangat mendukung dan melindungi ODHA dari stigma (Armoon et al, 2022).…”
Section: Analisis Data Stigma Sebelum Intervensi (Pretest)unclassified
“…Social stigma toward HIV and other infectious diseases has detrimental effects on several health-related outcomes. For example, HIV-related stigma is associated with severe anxiety and depression [ 17 ]. Pandemic-related work conditions are associated with adverse mental health and intention to leave the workplace [ 18 ].…”
Section: Introductionmentioning
confidence: 99%